An Exploration of EFL Student’s Expectation in English Department - Tanti Aprinia; Rahmat Setiawan (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study examines the gap between students' expectations and the reality of their learning experience in an EFL university setting. While students anticipate adequate facilities, a well-structured curriculum, and a supportive English-speaking environment, they often face inadequate resources, curriculum mismatches, and limited immersion. This disparity affects motivation, academic performance, and language proficiency. By identifying these gaps, the study offers insights for improving teaching strategies, curriculum development, and the overall EFL learning environment. This qualitative case study explores the gap between students' expectations and the reality of EFL learning in the English Education Department. Semi-structured interviews with three students from different academic levels provide diverse perspectives. Thematic analysis identifies key discrepancies in facilities, curriculum relevance, and the English-speaking environment. Expert validation ensures the validity of interview questions. Findings highlight the need for institutional improvements to enhance students' learning experiences. This study explores the gap between English Education students' expectations and reality, impacting their learning. Key issues include inadequate facilities, a theory-heavy curriculum, and a lack of English use in daily communication, leading to reduced motivation and proficiency. Institutions must improve facilities, balance theory with practice, and foster an English-speaking environment to better prepare future educators.